Effect of visit-to-visit LDL-, HDL-, and non-HDL-cholesterol variability on mortality and cardiovascular outcomes after percutaneous coronary intervention. (December 2018) - Lee, Eun Young; Yang, Yeoree; Kim, Hun-Sung; Cho, Jae-Hyoung; Yoon, Kun-Ho; Chung, Wook Sung; Lee, Seung-Hwan; Chang, Kiyuk
Abstract: Background and aims: Visit-to-visit variability in biological measures has been suggested as an independent predictor of cardiovascular disease (CVD). Although low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C) are important risk factors of CVD, there are few studies investigating the effect of variability in LDL-C and HDL-C on cardiovascular outcomes. We investigated the association between visit-to-visit variability in LDL-C, HDL-C, and non-HDL-C and major adverse cardiovascular and cerebrovascular events (MACCE) in patients who underwent percutaneous coronary intervention (PCI). Methods: Data from 1792 subjects who underwent PCI from January 2004 to December 2009 were analyzed. Visit-to-visit variability was calculated using various indices: standard deviation (SD), coefficient of variation, and corrected variability independent of mean (cVIM). MACCE comprised all-cause death, non-fatal myocardial infarction, and stroke. Results: During a median follow-up period of 65 months, 114 subjects (6.4%) experienced MACCE: 68 (3.8%) all-cause death; 43 (2.4%) stroke, and 15 (0.8%) non-fatal myocardial infarction. Visit-to-visit variability in LDL-C, HDL-C, and non-HDL-C was significantly higher in the MACCE group compared to the non-MACCE group. In multiple regression analysis, all LDL-C, HDL-C, and non-HDL-C variability parameters were independent predictors for MACCE after adjusting for potential confounding factors. Each 1-SD increase of cVIM in LDL-C, HDL-C, and non-HDL-C increased the risk of MACCE by 34% (HR 1.34 [95% CI, 1.18–1.52]), 50% (HR 1.50 [95% CI 1.32–1.71]), and 37% (HR 1.37 [95% CI, 1.20–1.57]), respectively. These relationships were observed in various subgroups according to age, sex, and diabetes status. Conclusions: Visit-to-visit variability in LDL-C, HDL-C, and non-HDL-C is associated with MACCE in subjects with previous PCI. Highlights: Higher visit-to-visit non-HDL-cholesterol variability in MACCE group. Visit-to-visit LDL-, HDL-, and non-HDL-cholesterol variability can predict MACCE. Important dynamic relationship between cholesterol levels and clinical outcomes.